Cell cycle regulation of RPA1 transcript levels in the trypanosomatid Crithidia fasciculata. - Brown, L M (1997)
Transcripts of both mitochondrial and nuclear DNA replication genes accumulate periodically during the cell cycle in Crithidia fasciculata. An octameric consensus sequence with a conserved hexameric core was found previously to be required for cycling of the TOP2 transcript, encoding the mitochondrial DNA topoisomerase. We show here that the rate of synthesis of the p51 protein, the large subunit of nuclear replication protein-A encoded by the RPA1 gene, varies during the cell cycle in parallel with RPA1 mRNA level. Plasmids expressing a truncated form of RPA1 (Delta RPA1 ) were used to identify cis elements required for cycling of the Delta RPA1 transcript. Sequences within the RPA1 5'-untranslated region (UTR) were found to be necessary for cycling of the Delta RPA1 transcript. These sequences also function when transposed 3'of the Delta RPA1 coding sequence. A 121 bp fragment of this sequence can confer cycling on a heterologous transcript, but is inactivated when two consensus octamers within the sequence are mutated. Mutation of these two octamers in the full-length 5'-UTR ofDelta RPA1 is insufficient to abolish cycling of the mRNA unless three additional octamers having single base changes within the hexameric core are also mutated. Thus, common octameric sequence elements are involved in periodic accumulation of both the TOP2 and RPA1 transcripts.